2006
DOI: 10.1002/nme.1881
|View full text |Cite
|
Sign up to set email alerts
|

Discrete element method for modelling solid and particulate materials

Abstract: SUMMARYThe discrete element method (DEM) is developed in this study as a general and robust technique for unified two-dimensional modelling of the mechanical behaviour of solid and particulate materials, including the transition from solid phase to particulate phase. Inter-element parameters (contact stiffnesses and failure criteria) are theoretically established as functions of element size and commonly accepted material parameters including Young's modulus, Poisson's ratio, ultimate tensile strength, and fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
115
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(117 citation statements)
references
References 32 publications
0
115
1
1
Order By: Relevance
“…If the value of η is increased above unity, bonds are formed between particles which are not necessarily in direct contact, this is a similar formulation to models [e.g. [34][35][36] but different to others [e.g. 6] where physical particle overlap is required for a bond to form.…”
Section: Bond Initialisationmentioning
confidence: 78%
“…If the value of η is increased above unity, bonds are formed between particles which are not necessarily in direct contact, this is a similar formulation to models [e.g. [34][35][36] but different to others [e.g. 6] where physical particle overlap is required for a bond to form.…”
Section: Bond Initialisationmentioning
confidence: 78%
“…Within the discrete element approach, cracks are simulated by breaking bonds that reach a particular criterion (23,24,25,26,27,28). This approach mimics crack extension in a material.…”
Section: The Fracture Criterionmentioning
confidence: 99%
“…Since a Cartesian grid discretizes the ELDC geometry into 3D cells, detecting particle collisions for each particle is limited to the cell confining the target particle and the adjacent grid cells. DEM discretization promises to provide a better numerical convergence with refinement of the grid cells (Tavarez and Plesha, 2007). Sensitivity analysis on grid cell size demonstrated that grid sizes finer than 0.2 mm do not influence the obtained particle trajectories.…”
Section: Discrete Element Methodsmentioning
confidence: 99%
“…The time step in DEM modeling is a function of particle stiffness and mass of the smallest particle (Tavarez and Plesha, 2007). Depending on particle concentration, 20% to 40% of the Rayleigh time step has been suggested as the suitable time step for EDEM program.…”
Section: Discrete Element Methodsmentioning
confidence: 99%